A CROSS-DISCIPLINARY SUCCESSFUL AGING INTERVENTION PROGRAM: PERSON-TO-PERSON AND DIGITAL-ASSISTED APPROACHES. (11th November 2018) - Hsu, H; Lin, J; Kuo, T; Hsu, W; Yu, C; Chen, Y; Xie, W; Hsu, W
Abstract: Purpose: The purpose of this study was to implement and evaluate a cross-disciplinary successful aging intervention program by two approaches to improve for the community-based older adults in Taiwan. Methods: The cross-disciplinary intervention program was designed to improve successful aging. The content included successful aging concept and preparation, physical activity, chronic disease and health management, diet and nutrition, cognitive training, emotional awareness and coping, family relationship and resilience, financial protection law and concept, and internet use. Five community care centers in Taichung agreed to participate in this study. The intervention was given once per week for 3 months. The traditional person-to-person (P2P) intervention approach was implemented on the urban centers (n=61), and the personal-and-digital (P&D) intervention approached was implemented on the rural centers (n=54); the participants before the P&D group received intervention were assessed as the control group for comparison (n=32). Generalized estimating equation was applied for analysis. Result: Healthy behavior and nutrition were improved for P2P group although not significant. The adaption to old age and reducing ineffective coping significantly reduced for the P2P group; cognitive function and depressive symptoms improved for both experimental groups although not significant. The ability to search health information improved for the P&D group, and the knowledge for finance-related law increased for the P2P group. Area and educational differences existed. Conclusion: A continuous well-designed and evidence-based intervention program is beneficial for improving older adults' health or delaying health decline. The P2P approach seems more effective than the P&D approach for the current older generation.